Analysis of user behavior and authorization methods in context of mobile devices security - Król, Piotr; Marek, Damian; Smołka, Jakub (Journal of Computer Sciences Institute, 2018)
This article discusses authentication methods for users of mobile devices with touchscreens. The analysis concerns the authentication methods already existing in Android OS and new authorization methods proposed by the authors. Pattern and PIN (Personal Identification Number) lock were compared with two new authentication methods. The time required for entering the key, number of mistakes, number of possible combinations were analyzed.